2000
DOI: 10.1177/019251300021003004
|View full text |Cite
|
Sign up to set email alerts
|

Identity Theory as a Guide to Understanding Fathers' Involvement With Their Children

Abstract: Identity theory was used to explore fathers' involvement with their children. Eighty-nine married couples with preschool children completed questionnaires and interviews providing information on how involved they were in child-rearing activities. Participants rated the centrality of their parent versus worker status and of the nurturing role. Results indicated that fathers did not differ on any involvement measures regardless of whether they rated the parent or worker status most central. However, fathers who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
175
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(196 citation statements)
references
References 26 publications
12
175
1
8
Order By: Relevance
“…Fatherhood should also be examined in relation to motherhood, particularly because the couple context seems to shape the importance of fatherhood for men (Cook et al, 2005;Henley & Pasley, 2005;Rane & McBride, 2000) and because meanings of motherhood have also shifted in the last several decades. Although women are often depicted as making "hard choices" between work and motherhood (Blair-Loy, 2001;Gerson, 1985;Williams, 2000), McQuillan et al (2008) find that women place a high value on both, just as men do.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fatherhood should also be examined in relation to motherhood, particularly because the couple context seems to shape the importance of fatherhood for men (Cook et al, 2005;Henley & Pasley, 2005;Rane & McBride, 2000) and because meanings of motherhood have also shifted in the last several decades. Although women are often depicted as making "hard choices" between work and motherhood (Blair-Loy, 2001;Gerson, 1985;Williams, 2000), McQuillan et al (2008) find that women place a high value on both, just as men do.…”
Section: Discussionmentioning
confidence: 99%
“…), typically using a penny sort (Rane & McBride, 2000) or pie chart (Habib & Lancaster, 2006) methodology. Research on fathering has generally found that centrality is more important than salience in explaining fathering behavior (Henley & Pasley, 2005;Rane & McBride, 2000).…”
Section: Identity Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…De plus, l'im pli ca tion pa ter nelle peut pren dre la forme d'ac ti vi tés tra di tion nel les (par exemple, nour rir l'en fant, changer sa cou che) ou de par ti ci pa tion au jeu (Ra din, 1994). Fi na le ment, elle peut être con cep tua li sée d'un point de vue intra-psychique comme une va leur que le père y ac corde (Bei tel et Parke, 1998) ou quand la pa ternité fait par tie de l'iden tité d'un homme (Rane et McBride, 2000). Et comme l'im pli ca tion pa ren tale, quelle que soit sa dé fi ni tion, est plus sus cep ti ble de va rier pour les pè res tant en quan tité qu'en qua lité (Parke, 1996), il est es sen tiel d'en avoir une pers pec tive mul ti di men sion nelle, au-delà des mo dè les tra di tion nels fé mi nins, lorsqu'on con si dère leur rôle dans ce par te na riat.…”
unclassified